Factors affecting the distribution of two Synechococcus ecotypes in the coastal Adriatic Sea - Šantić, Danijela (Array, 2018)
Distribution and abundance of two Synechococcus ecotypes, phycocyanin-rich cells (PC-SYN) and phycoerythrin-rich cells (PE-SYN) were studied in the surface layer of the central Adriatic Sea during the 2015-2016 period. The studied area included several estuarine areas and coastal to open sea trophic gradients, covering a wide range of seawater temperatures \((11.82 - 20.75 oC)\), salinity (4.47 - 38.84) and nutrient concentration. The abundance of PC-SYN ranged from \( 0 to 79.79 x 10 3 cell mL -1\) and that of PE-SYN from \(5.01 x 10 3 to 76.74 x 10 3 cell mL -1\). Both ecotypes coexisted in the studied waters with PC-SYN cells dominating during spring and PE-SYN during winter and autumn. PC-SYN showed a significant positive relationship with temperature and strong positive responses to nitrogen nutrients, whereas PE-SYN positively responded to phosphate availability. The relative ratio of phosphorus availability and total inorganic nitrogen nutrients (N/P ratio) affects the spatial distribution of the two Synechococcus ecotypes.